FORMATION OF THE INVESTMENT PORTFOLIO ON THE BASIS OF THE CAPM - Yulia Konopleva (Вестник Северо-Кавказского федерального университета, 2022)
The article describes a popular model for evaluating capital assets CAPM. Studied the method offorming an efficient investment portfolio, using this model. Unlike investigated by the CAPM model, the index W. Sharpe. The basic principles for the selection of the investment portfolio. Studied the main results ofthe model CAPM, is to divide, which shows the optimal combination of assets in the portfolio without taking into account the investor's subjective preferences. The advantages and disadvantages of the model under investigation. In connection with the identified shortcomings in the model of CAPM, we investigated the modified capital asset pricing model. Included in these additional parameters are created only in order to increase the accuracy offorecasting for efficient portfolio.